Experimental Study of Concentrated Solar Power on Heat Feed Water Heaters in Steam Power Plants in Iraq - Khudor, Dhamyaa Saad; Abdulsada, Ghanim Kadhim; Issa, Moumin Mahdi (Journal of Petroleum Research and Studies, 2021)
For generating power, solar energy is counted a good exporter. Iraq is located in a hot zone with latitude from 32 degree N to 36 degree N. In Iraq, the average solar radiation is about 7 kilowatt hours / day. In this work, central receiving tower was used to obtain steam using the available solar energy in summer and winter. To heat the feed water heater of South Baghdad Electrical Steam Power Plant, steam utilization for this purpose. In the project, manufacturing the central receiver tower, which is consisting of 150 mirrors fixed upon 75 manual tracking heliostats arranged for utilization the solar radiation concentrated on the central receiving tank (CRT). Pipes systems were used for hot water or steam exits from receiver. In this study, the central receiver tank (0.5m*1m) was filled with 157 liter of water. The experimental work was run for one year from June 2015 – May 2016. The outlet temperature of water from central tower receiver was steam for (July and August 2015) and hot water with high temperature for other months of the year. The results obtained from our system, solar shares for heating the feed water heater of South Baghdad Electrical Steam Power Plant up to 1.86 % and an annual average of 1.03%. Temperature, power concentration factor and system efficient are greatly influenced by the number of heliostats used. A sample of calculations is used to evaluate the mathematical data of hot water and steam temperatures obtained from this study. These values are approximate with experimental data when compared together.